Seasonal characteristic of gonadogenesis for the sea cucumber Apostichopus japonicus Selenka - Inga V. Matrosova; Vladimir V. Evdokimov (Известия ТИНРО, 2016)
Gonads of females and males of the sea cucumber Apostichopus japonicus were collected along Primorye coast of the Japan Sea (bays Kiyevka, Sokolovskaya, Melkovodnaya, Sredniaya, and the area between Cape Genbachev and Cape DeLivron) in different seasons from May to October, 2011. The gonads were fixed in 70 % alcohol and Buena fixing agent, using Isoprep and Histomix, and subjected to histophyisiological analysis. Sex of the animals and condition of their gonads were defined visually and on histological preparations. Their whole bodies, skin and muscular bags, and sexual glands were weighted, gonad-somatic indices were calculated, dynamics of cellular composition was traced for the sex glands, timing of spawning and duration of the rest stage were determined. For the cucumbers from the Kiyevka and Melkovodnaya Bays, diameter of sex tubules varied from 0.2 mm to 1.9 mm, diameter of freely lying oocytes - from 71.4 mm to 167.0 mm, and diameter of wall oocytes - from 47.6 mm to 119.0 mm; they were ready for spawning in late July - early August, and spawned in the first 10-days of August. Plication of the tubule walls internal surface was observed later in the process of mature cells resorption in sex tubules; new generation of the cells appeared, which most likely would undergo to further destruction (small tubules with plication of their walls were observed for a specimen from the Kiyevka Bay in late September, 2011). New gametogenesis was registered both for females (small oocytes) and males (spermatocytes of I and II orders) from the Sredniaya Bay and between Cape Genbachev and Cape DeLivron in early October, simultaneously with continuing process of the tubule walls plication. The rest stage (without forming of new sex tubules) continued 1.0-1.5 months: from early August to middle September, with some variations between the areas.